Multidecadal trends in aerosol radiative forcing over the Arctic: Contribution of changes in anthropogenic aerosol to Arctic warming since 1980. Issue 6 (16th March 2017) - Breider, Thomas J.; Mickley, Loretta J.; Jacob, Daniel J.; Ge, Cui; Wang, Jun; Payer Sulprizio, Melissa; Croft, Betty; Ridley, David A.; McConnell, Joseph R.; Sharma, Sangeeta; Husain, Liaquat; Dutkiewicz, Vincent A.; et al.
Abstract: Arctic observations show large decreases in the concentrations of sulfate and black carbon (BC) aerosols since the early 1980s. These near‐term climate‐forcing pollutants perturb the radiative balance of the atmosphere and may have played an important role in recent Arctic warming. We use the GEOS‐Chem global chemical transport model to construct a 3‐D representation of Arctic aerosols that is generally consistent with observations and their trends from 1980 to 2010. Observations at Arctic surface sites show significant decreases in sulfate and BC mass concentrations of 2–3% per year. We find that anthropogenic aerosols yield a negative forcing over the Arctic, with an average 2005–2010 Arctic shortwave radiative forcing (RF) of −0.19 ± 0.05 W m −2 at the top of atmosphere (TOA). Anthropogenic sulfate in our study yields more strongly negative forcings over the Arctic troposphere in spring (−1.17 ± 0.10 W m −2 ) than previously reported. From 1980 to 2010, TOA negative RF by Arctic aerosol declined, from −0.67 ± 0.06 W m −2 to −0.19 ± 0.05 W m −2, yielding a net TOA RF of +0.48 ± 0.06 W m −2 . The net positive RF is due almost entirely to decreases in anthropogenic sulfate loading over the Arctic. We estimate that 1980–2010 trends in aerosol‐radiation interactions over the Arctic and Northern Hemisphere midlatitudes have contributed a net warming at the Arctic surface of +0.27 ± 0.04 K, roughly one quarter of the observed warming. Our study does not consider BC emissions from gas flaring nor the regional climate response to aerosol‐cloud interactions or BC deposition on snow. Key Points: Observed sulfate and BC mass concentrations at Arctic surface sites and Greenland ice cores show decreases of 2–3%/yr between 1980 and 2010 Anthropogenic aerosol RF is negative in the Arctic troposphere due to a large negative RF from sulfate in spring (−1.17 ± 0.10 W m −2 ) The 1980–2010 trends in aerosol‐radiation interactions over the Arctic and NH midlatitudes contributed 0.27 ± 0.04 K warming at Arctic surface